Sunlight Photocatalytic Degradation of Propanil in Aqueous Solution and Determination of Degraded Products with UV-and HPLC - A. Dhahir, Saadiyah (Asian Journal of Chemistry, 2012)
The solar photocatalytic of an aqueous propanil were carried out under natural weathering conditions. Photocatalytic of 20 μg/mL propanil solution degraded 95 % of the solution after 3 h of solar irradiation, by using 10 mg of zinc oxide as a catalyst. The effect of various parameters such as amount of catalyst and illumination time on the degradation of propanil has been studied. The degradation percentages were investigated by monitoring the propanil mineralization spectrophotometrically. The mineralization rate of propanil is calculated.